2016
DOI: 10.1136/jech-2016-207707
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of economic growth and plummeting mortality: the mortality experience of the poorly educated in South Korea

Abstract: The South Korean experience over the past 40 years suggests that plummeting mortality rates and huge advances in education at the population level do not translate into reduced educational inequalities in mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…Several previous studies examined socioeconomic inequality in mortality and LE over the past decades in Korea and found an unabated trend towards inequality 5 26 27. The increase in LE inequality according to education was clearer in women than in men 27.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several previous studies examined socioeconomic inequality in mortality and LE over the past decades in Korea and found an unabated trend towards inequality 5 26 27. The increase in LE inequality according to education was clearer in women than in men 27.…”
Section: Discussionmentioning
confidence: 92%
“…Socioeconomic inequalities in LE rather than socioeconomic inequalities in mortality or health behaviours might be better accepted as the overarching target for health equity to the public. A recent study showed that both relative and absolute educational inequality in mortality had not decreased in the four decades since 1970 in Korea 5. Each socioeconomic position (SEP) indicator has distinct influences in promoting or damaging population health 6.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is unexpected, since absolute differences in all-cause mortality according to socioeconomic position are generally greater in men than in women [25]. Prior Korean studies also showed that absolute differences in all-cause mortality and life expectancy according to socioeconomic position indicators, such as education and income, were greater in men than in women [26,27,28]. Two possible explanations can be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the recent increase in the numbers of older people in developed countries is a consequence of advances in hygiene and biomedicine as well as an artefact of human civilization [21]. In particular, South Korea has experienced rapid economic development and a substantial increase in life expectancy in an extremely short period, between 1970 and 2010, mainly due to the rapid processes of industrialization and urbanization [22,23].…”
Section: Discussionmentioning
confidence: 99%